Perbandingan Kurikulum Merdeka di Indonesia dan Kurikulum Nasional di Jepang: Kajian Konseptual dan Praktis - Muhammad Jitu; Wahyuni Fitri; Elsi Fitrianis; Aprizal Ahmad (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to compare the Merdeka Curriculum in Indonesia and the National Curriculum in Japan from both conceptual and practical perspectives. The analysis focuses on the fundamental principles, educational goals, learning approaches, and classroom implementation. Indonesia’s Merdeka Curriculum emphasizes flexibility and autonomy for teachers and students, highlighting competency development, character building, and the Profil Pelajar Pancasila (Pancasila Student Profile). Meanwhile, Japan’s National Curriculum centers on fostering a well-balanced personality through integrated moral, social, and academic education. Conceptually, both curricula share similarities in promoting holistic learning and character education, yet they differ in implementation and assessment systems. In Indonesia, project-based and differentiated learning approaches are key features, whereas Japan emphasizes collaborative learning, discipline, and hands-on experience in daily life. Practically, Indonesia faces challenges in ensuring equal access to resources and teacher readiness, while Japan has established a stable and standardized national education system. This comparative analysis reveals that Indonesia can learn from Japan in terms of consistency, learning culture, and the integration of moral and social values. Thus, the study provides valuable insights for enhancing Indonesia’s curriculum to become more globally responsive while preserving national identity and character.